2019
DOI: 10.3390/su11010242
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Transitions and Socioeconomic Development in Italy, 1862–2009: A Brief Overview

Abstract: The present study investigates long-term population dynamics in Italy, 1862–2009, in light of Demographic Transitions (DTs). Under the assumption that DTs are multidimensional processes of change involving several aspects, including population structure and dynamics, an exploratory analysis was carried out in this study to verify temporal coherency of 15 indicators in Italy, identifying homogeneous time periods with distinct demographic characteristics. Indicators’ trends were identified using a multivariate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
(89 reference statements)
0
11
0
4
Order By: Relevance
“…The originality of our contribution stems from the in-depth view it provides of the association between the declines in fertility and mortality from both an individual and an aggregate perspective. In Villagrande and Seulo, as elsewhere in Sardinia, these fertility and mortality transitions occurred later than they did in the rest of Italy (Livi-Bacci 1977;Breschi 2012;Salvati et al 2019). General fertility dropped below the replacement level in the 1970s as the result of a decrease in marital fertility and a rise in the proportion of women who did not marry up to the end of their reproductive span.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The originality of our contribution stems from the in-depth view it provides of the association between the declines in fertility and mortality from both an individual and an aggregate perspective. In Villagrande and Seulo, as elsewhere in Sardinia, these fertility and mortality transitions occurred later than they did in the rest of Italy (Livi-Bacci 1977;Breschi 2012;Salvati et al 2019). General fertility dropped below the replacement level in the 1970s as the result of a decrease in marital fertility and a rise in the proportion of women who did not marry up to the end of their reproductive span.…”
Section: Discussionmentioning
confidence: 96%
“…Cultural and social factors conditioned the reproductive behaviour of couples, but mortality may have also been affected by (temporal) socio-economic and political conditions. Livi (1961) and, more recently, Salvati et al (2019) identified a period between the two world wars as a particularly relevant turning point in demographic dynamics. A similar period was noted during the 1970s.…”
Section: Year Of Birth Of the Last Childmentioning
confidence: 99%
“…In China, demographic transition has provided a window of opportunity for economic growth and the potential for socioeconomic development (Yuan & Gao, 2020). The process of modernization in economically-advanced countries such as Italy is intended to shift to new types of social, economic, and political systems which are closely linked to demographic transition (Salvati et al, 2019).…”
Section: Theoretical Issues and The Literaturementioning
confidence: 99%
“…Países da Europa como a Itália, Alemanha e Grécia já enfrentam os efeitos do final da transição demográfica (Salvati, Carlucci, Serra, & Zambon, 2019), quando suas taxas de fecundidade e mortalidade se encontram em níveis baixos e o crescimento da população é próximo de zero. Como pode ser visto nos Gráficos 09 e 10, a fecundidade desses países se encontram abaixo de nível de reposição (2,1 por mulher), em torno de 1,5 na Alemanha, 1,3 na Grécia e 1,4 na Itália, em 2016, e a taxa de mortalidade também se encontra em níveis baixos.…”
Section: Implicações Do Envelhecimento Populacional Na Previdência Sounclassified